Efforts to Increase Students' Understanding of the Position and Role of Family Members Through Concrete Demonstrations at MI Al Huda Mangli - Fajar (Indonesian Journal of Education and Social Humanities, 2024)
This research aims to improve students' understanding of the material "Position and Role of Family Members" through the use of learning media in the form of concrete models at Madrasah Ibtidaiyah Al Huda Mangli. The background of this research is the low level of students' understanding of the material, which is shown through the results of learning evaluations that have not yet reached the Minimum Completion Criteria (KKM). The method used in this research is Classroom Action Research (PTK) with two cycles, each of which consists of planning, implementation, observation, and reflection. The subjects of the research are 24 class II students of MI Al Huda Mangli. Data collection techniques include observation, interviews, tests, and documentation. The results of the research show that the use of concrete props can improve students' understanding of the material being taught. This can be seen from the increase in learning evaluation results in each cycle. In cycle I, the average score of students increased compared to before the action, but there are still some students who have not reached the KKM. After improvements were made in cycle II, student learning outcomes experienced a significant increase with the percentage of learning completion reaching 91.6%. In addition, students' learning activities also showed an increase, marked by an increase in active participation, enthusiasm, and students' ability to verbally explain the position and role of family members. The use of concrete props is proven to help students understand abstract concepts to be more real and easy to understand. Thus, it can be concluded that the use of concrete props is an effective learning strategy in improving students' understanding of IPS material, especially the theme of the position and role of family members. This research recommends that teachers use concrete props more often in the learning process, especially for material that is conceptual and requires real visualization so that it is easier for early learners to understand.